Fundamentals for the Automation of Object-Relationa Database Design - Golobisky, María Fernanda (2011)
In the market there is a wide amount of CASE tools for the design of relational databases. Object-relational database management system (ORDBMS) emerged at the end of the 90?s to incorporate the object technology into the relational databases, allowing the treatment of more complex data and relationships than its predecessor. The design for this database model is not straightforward. Most of the works proposed in the literature fail because they do not provide consistent transformation formalization such that the mappings from the conceptual model to the logical schema can be automated to generate an ORDB design toolkit. This is one of the goals of this paper. For this purpose, UML class diagram metamodel for the conceptual design and SQL:2003 standard metamodel for logical schemas are considered. A characterization of the components involved in the ORDB design is made in order to propose mapping rules that can be further automated. The architecture of a CASE tool prototype is presented. Model Driven Architecture for software design and XML for the model definitions and transformations are employed.